EL APRENDIZAJE COLABORATIVO Y SU IMPACTO EN LA EDUCACIÓN INCLUSIVA DE LOS ESTUDIANTES DEL NOVENO AÑO EGB DE LA ESCUELA DE EDUCACIÓN BÁSICA ISABEL LA CATÓLICA Y NOVENO AÑO DE EGB DE LA UNIDAD EDUCATIVA JUAN E VERDESOTO DE LA PARROQUIA CAMILO PONCE ENRÍQUEZ DEL CANTÓN BABAHOYO PERÍODO ACADÉMICO 2024 - 2025 - JÁCOME BAJAÑA DAHIANA BELÉN (2024)
Collaborative learning is very important for the development of students' skills, helping to promote an inclusive environment allowing the participation of all students. The focus of the present research project was aimed at determining the impact of collaborative learning on inclusive education in ninth-grade students at Isabel la Católica Basic Education School and ninth-grade students at Juan E. Verdesoto Educational Unit. It is crucial to foster an inclusive environment in the classroom allowing the participation of all students, and the implementation of this strategy can be key to achieving this objective. A mixed methodology was chosen to obtain data for this project because through this approach, quantitative and qualitative data can be collected to gain a deeper understanding of the topic in the selected institutions for research. Additionally, the research level was explanatory in order to study the problem more profoundly. Within the study, it was found that a large part of the students show a good level of acceptance towards the implementation of activities involving collaborative learning in the classroom. Furthermore, there are certain factors that hinder this educational strategy and teachers strive to make inclusive education a reality in the classroom every day despite the difficulties that may arise in the school environment.